2020
DOI: 10.1126/sciadv.abc4397
|View full text |Cite
|
Sign up to set email alerts
|

On the shuttling across the blood-brain barrier via tubule formation: Mechanism and cargo avidity bias

Abstract: The blood-brain barrier is made of polarized brain endothelial cells (BECs) phenotypically conditioned by the central nervous system (CNS). Although transport across BECs is of paramount importance for nutrient uptake as well as ridding the brain of waste products, the intracellular sorting mechanisms that regulate successful receptor-mediated transcytosis in BECs remain to be elucidated. Here, we used a synthetic multivalent system with tunable avidity to the low-density lipoprotein receptor–related protein 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 54 publications
9
86
0
1
Order By: Relevance
“…Based on these findings, it was thus hypothesised that PACSIN-2 mediates vesicle or tubule formation for endocytosis. Interestingly, our recent study demonstrated that PACSIN-2 participates in the formation of tubular carriers for a fast transcytosis of LRP1 across BECs [7]. Furthermore, we also demonstrated that BECs employ PACSIN-2 for the clearance of amyloid-ß via LRP1 across the BBB [84].…”
Section: Endocytosissupporting
confidence: 51%
See 4 more Smart Citations
“…Based on these findings, it was thus hypothesised that PACSIN-2 mediates vesicle or tubule formation for endocytosis. Interestingly, our recent study demonstrated that PACSIN-2 participates in the formation of tubular carriers for a fast transcytosis of LRP1 across BECs [7]. Furthermore, we also demonstrated that BECs employ PACSIN-2 for the clearance of amyloid-ß via LRP1 across the BBB [84].…”
Section: Endocytosissupporting
confidence: 51%
“…A generally established concept is that endosomes undergo maturation, starting from the initial early endosomes (within 1-5 min, vesicles positive for Rab5 and early endosome antigen 1, EEA1), late endosomes (10-15 min, Rab7-positive vesicles) and lysosomes for degradation (after 30 min of the initiation of CME in vesicles associated with a lysosomal-associated membrane protein 1, LAMP1) [115]. However, this timing (15 to 30 min) is inconsistent with the rapid rate of transcytosis observed in vivo, which has been found to occur in <60 s in the lung epithelium [85] and even faster in BECs [7,117].…”
Section: Intracellular Trafficking: Spherical Versus Tubular Carriersmentioning
confidence: 97%
See 3 more Smart Citations